Impact of Sex Hormones on Macrophage Responses to Coxiella burnetii - Gay, Laetitia; Melenotte, Cléa; Lopez, Alexandre; Desnues, Benoit; Raoult, Didier; Leone, Marc; Mezouar, Soraya; Mege, Jean-Louis (Frontiers in Immunology, 2021)
Introduction: Q fever, a zoonosis caused by Coxiella burnetii, affects more males than females despite a similar level of exposure. A protective role of estradiol has been reported in mice, suggesting that sex hormones are involved in C. burnetii infection. We wondered whether the responses of monocytes and monocyte-derived macrophages (MDMs) to C. burnetii are influenced by sex hormones. Materials and Methods: The bacterial intracellular fate in monocytes was studied using quantitative PCR, and monocyte cytokine production in response to C. burnetii was assessed using qRT-PCR and immunoassays. Before infection, MDMs from males and females were incubated with testosterone and estradiol, respectively. Results: Bacterial uptake and persistence were similar in monocytes from males and females but were slightly increased in male MDMs. The expression of inflammatory genes, including those encoding TNF and CXCL10, was higher in MDMs from females than in MDMs from males infected by C. burnetii. Adding testosterone to male MDMs amplified their immunoregulatory properties, including increased expression of IL10 and TGFB genes and TGF-β production in response to C. burnetii. In contrast, adding estradiol to MDMs from females had no effect on their inflammatory profile. Conclusion: The stronger inflammatory profile of macrophages from females may have a protective role, likely under estrogen control, while testosterone may affect disease progression by promoting an anti-inflammatory response. This finding may have consequences for personalized management of patients with Q fever.